Liar, Liar, Head On Fire - Strange, Vera (Los Angeles : Disney Press, 2021)
Twelve-year-old Hector's family is counting on him to win the Zeus Cup in a race, but when a Greek god offers a deal to help him win, all Hades breaks loose.
Ages 8-12.
Grades 7-9.
Keywords: Hades -- (Greek deity) -- Fiction; Racing -- Fiction; Family life -- Fiction; Horror stories; Hispanic Americans -- Fiction; Mythology, Greek -- Fiction